2022
DOI: 10.1111/xen.12744
|View full text |Cite
|
Sign up to set email alerts
|

Progressive genetic modifications of porcine cardiac xenografts extend survival to 9 months

Abstract: We report orthotopic (life‐supporting) survival of genetically engineered porcine cardiac xenografts (with six gene modifications) for almost 9 months in baboon recipients. This work builds on our previously reported heterotopic cardiac xenograft (three gene modifications) survival up to 945 days with an anti‐CD40 monoclonal antibody‐based immunosuppression. In this current study, life‐supporting xenografts containing multiple human complement regulatory, thromboregulatory, and anti‐inflammatory proteins, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 49 publications
0
88
0
2
Order By: Relevance
“…We fully recognize the immense effort put into the care of this patient by the Maryland team, and we applaud the willingness of the patient to undergo such an experimental procedure. months, 4,51 with these grafts being lost through antibody-mediated rejection. Although, in the absence of the problems associated with the 4 th xenoantigen, 5,11 the results in humans may be superior to those in NHPs, the outcome for a patient with a pig heart graft remains uncertain.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…We fully recognize the immense effort put into the care of this patient by the Maryland team, and we applaud the willingness of the patient to undergo such an experimental procedure. months, 4,51 with these grafts being lost through antibody-mediated rejection. Although, in the absence of the problems associated with the 4 th xenoantigen, 5,11 the results in humans may be superior to those in NHPs, the outcome for a patient with a pig heart graft remains uncertain.…”
Section: Commentmentioning
confidence: 99%
“…The Maryland team had obtained encouraging results from pig orthotopic heart transplantation in baboons 2–4 . Using essentially the same genetically‐engineered pigs (with 10 genetic modifications) and immunosuppressive regimen (based on blockade of the CD40/CD154 co‐stimulation pathway), one would have anticipated an equally encouraging result from their first clinical effort, particularly as the high prevalence of a positive cross‐match against “triple‐knock‐out” (TKO) pigs, likely associated with a putative “4 th xenoantigen” recognized by nonhuman primates (NHP), 5–8 is not observed in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial heart xenotransplants in non-human primates displayed a median survival of 298 days with an immunosuppression regime of MMF and anti-CD40 antibodies [45]. Similar studies using genetically modified heart xenografts demonstrated that the use of cold perfusion to preserve the donor heart reduced the incidence of perioperative cardiac xenograft dysfunction compared to SCS [40,46,47 [48] expanded the genetic modification of porcine donor hearts by using a maximum of nine modifications: insertions that regulate complement activation (hCD46, hDAF), coagulation (hTBM, hEPCR) and inflammation (hCD47, hHO-1), and deletions to minimize porcine cell antigenicity (GGTA1, B4GalNT2, CMAH) and cell growth (growth hormone receptor). In addition, cold perfusion was used for donor heart preservation in all but two donor porcine hearts.…”
Section: Xenotransplantationmentioning
confidence: 93%
“…17 Nevertheless, the heart appeared to develop overgrowth and thickening of the myocardium, with diastolic dysfunction resulting in ascites and heart failure. 18 The addition of growth hormone receptor knockout appeared to decrease this myocardial thickening, with diastolic dysfunction and extended survival past 9 months when added to genetic modifications of GTKO, b1,4-N-acetylgalactosyltransferase, hTBM, hCD46, hCD47, humanized heme oxygenase-1, decay-accelerating factor, and endothelial protein C receptor. 18 Anesthetic Care for Pig-to-Baboon Cardiac Xenotransplants…”
Section: Genetic Engineering Toward the First Genetically Modified Pi...mentioning
confidence: 99%